kNACking on heaven’s door: how important are NAC transcription factors for leaf senescence and Fe/Zn remobilization to seeds? - Ricachenevsky, Felipe K.; Menguer, Paloma K.; Sperotto, Raul A. (Frontiers in Plant Science, 2013)
Senescence is a coordinated process where a plant, or a part of it, engages in programmed cell death to salvage nutrients by remobilizing them to younger tissues or to developing seeds. As Fe and Zn deficiency are the two major nutritional disorders in humans, increased concentration of these nutrients through biofortification in cereal grains is a long-sought goal. Recent evidences point to a link between the onset of leaf senescence and increased Fe and Zn remobilization. In wheat, one member of the NAC transcription factor family (NAM-B1) has a major role in the process, probably regulating key genes for the early onset of senescence, which results in higher Fe and Zn concentrations in grains. In rice, the most important staple food for nearly half of the world population, the NAM-B1 orthologue does not have the same function. However, other NAC proteins are related to senescence, and could be playing roles on the same remobilization pathway. Thus, these genes are potential tools for biofortification strategies in rice. Here we review the current knowledge on the relationship between senescence, Fe and Zn remobilization and the role of NAC transcription factors, with special attention to rice. We also propose a working model for OsNAC5, which would act on the regulation of nicotianamine (NA) synthesis and metal-NA remobilization.